2021
DOI: 10.3389/fimmu.2021.653030
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Immune Escape Mechanism of Acute Myeloid Leukemia With DNMT3A Mutation

Abstract: DNA (cytosine-5)-methyltransferase 3A (DNMT3A)-mutated acute myeloid leukemia (AML) has a poor prognosis, but the exact mechanism is still unclear. Here, we aimed to explore the mechanism of immune escape in AML with DNMT3A mutation. We constructed a DNMT3A knockout clone and DNMT3A-R882H-mutated clones. RNA-seq results showed that transcription factors and macrophage inflammatory proteins were significantly downregulated in the DNMT3A mutant clones. KEGG enrichment and gene set enrichment analysis (GSEA) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…The DNMT3A mutant SKM‐1 cells were donated by Prof. Dengju Li. For detailed construction methods and related data, please refer to previous research 22 . The brief process was as follows: a lentiviral vector pCDH‐EF1‐MCS‐T2A‐copGFP was used to clone the full‐length human DNMT3A cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNMT3A mutant SKM‐1 cells were donated by Prof. Dengju Li. For detailed construction methods and related data, please refer to previous research 22 . The brief process was as follows: a lentiviral vector pCDH‐EF1‐MCS‐T2A‐copGFP was used to clone the full‐length human DNMT3A cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…For detailed construction methods and related data, please refer to previous research. 22 The brief process was as follows: a lentiviral vector pCDH-EF1-MCS-T2A-copGFP was used to clone the full-length human DNMT3A cDNA. Mutant strain of DNMT3A-R882H (CGC > CAC) was identified by DNA sequence.…”
Section: Construction Of Dnmt3a-r882h Mutant Cell Linementioning
confidence: 99%
“…Due to the growing evidence that leukemic cells interact with bone marrow (BM) reactive cells, including macrophages, the concept of leukemia-associated macrophages has been formulated [ 39 , 40 ]. A possible correlation between an immunosuppressive microenvironment and leukemia progression has been hypothesized for acute lymphoblastic leukemia (ALL), adult T-cell leukemia/lymphoma (ATLL), acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) [ 41 ].…”
Section: Tam Role In Leukemiamentioning
confidence: 99%
“…A possible correlation between an immunosuppressive microenvironment and leukemia progression has been hypothesized for acute lymphoblastic leukemia (ALL), adult T-cell leukemia/lymphoma (ATLL), acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) [ 41 ]. The pathophysiology could be linked at least in part to an immune escape, due to a reduced ability of macrophages to recognize antigens and to perform their phagocytosis [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Tam Role In Leukemiamentioning
confidence: 99%
“…DNMT3A mutation happened in a variety of cancers such as colorectal cancer, lung cancer, chronic myelocytic leukemia, but is mainly with AML [32][33][34] and usually occur with other types of mutations, such as FLT3, NPM1, C/EBP alpha, resulting in synergistic effects in AML [35][36][37]. Being the most common mutation, DNMT3A R882H mutation can not only lower methylation enzymatic activity [38,39] but can also co-act with other proteins to influence immune activity, cell apoptosis, proliferation, and DNA damage repair to regulate AML [40][41][42]. Researchers also found that Twist1, mTOR pathway, CDK1, and Dot1l [43][44][45][46] which might be the potential therapeutic targets of AML patients carry DNMT3A mutation.…”
Section: Discussionmentioning
confidence: 99%